(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The ethanol extract of Abutilon indicumL., Alangium salvifolium and Broussonetia papyriferaL. Silver Nanoparticles (AgNPs) was tested for hepatoprotective activity against paracetamol- convinced hepatotoxicities in rats. AAbutilon indicumL., Alangium salvifolium and Broussonetia papyriferaL. AgNPs displayed significant hepatoprotective activity by reducing paracetamol- convinced change inbiochemical parameters that was apparent by enzymatic examination. The factory extract may intrude with free-revolutionary conformation, which may conclude in hepatoprotective action.